Celebrating Eng’s First Impact Factor: A Milestone for Our Growing Journal - Antonio Gil Bravo (Eng, 2025)
It is with great pleasure that we announce Eng has received its first official Impact Factor in the 2024 Journal Citation Reports® [...]